ACUTE APPENDICITIS IN ELDERLY AND SENILE PATIENTS: MODERN APPROACHES TO DIAGNOSIS AND TREATMENT (International journal of medical sciences, 2026)
Acute appendicitis (AA) is the most common acute abdominal disease, with an incidence of 4-5 cases per 1,000 people. Postoperative complications after appendectomy range from 5% to 9%, and the mortality rate for this condition is 0.1-0.3%.